Cross-Border Matrimonial Disputes, the Applicability of the Hindu Marriage Act, 1955 and The Hague Convention on Civil Aspects of Child Abduction: An Analytical Study (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The globalization era has led to an increase in cross-border matrimonial disputes, raising complex legal questions about jurisdiction, domicile, and the applicability of domestic laws to individuals residing abroad. This article delves into the intricate legal issues surrounding the applicability of the Hindu Marriage Act, 1955, to parties of Indian origin who have acquired foreign citizenship but maintain domicile in India. Through an anonymized case study, the article examines the concepts of domicile, jurisdiction, enforcement of foreign judgments, and the grounds for divorce, maintenance, and property division under Indian law.